New species and host plant records for Neotropical Rhagoletis Loew (Diptera: Tephritidae) - Rodriguez, Pedro Alexander; Norrbom, Allen L.; Caicedo, Guadalupe; Peñaranda, Emilio Arévalo; Balseiro, Francisco (Zootaxa, 2021)
Rhagoletis antioquiensis Rodriguez & Norrbom, a new species of fruit fly in the striatella species group of Rhagoletis Loew, is described and illustrated. New distribution records are reported for two other species of the striatella group: R. nicaraguensis Hernández-Ortiz & Frías, 2000 is reported from Costa Rica, and R. solanophaga Hernández-Ortiz & Frías, 2000 from Bolivia. A lectotype is designated for Urophora scutellaris Macquart, 1851 (= R. macquartii (Loew)). New host plant relationships for three species of Rhagoletis, all reared from fruits, are reported: Acnistus arborescens (L.) Schrtdl. and Witheringia solanacea L’Her for R. jamaicensis Foote, 1981 from Colombia; Lycianthes pseudolycioides (Chod. & Hassl.) Bitter for R. solanophaga from Bolivia; and Solanum pseudocapsicum L., Solanum tuberosum L. subsp. andigenum (Juz. & Burkasov) Hawkes, Solanum interandinum Bitter from Colombia and Solanum americanum Mill. in Peru for undetermined species of the psalida group. The key to species of the striatella group of Hernández-Ortiz & Frías (2000) is modified to include R. antioquiensis.